2017
DOI: 10.1371/journal.pone.0177063
|View full text |Cite
|
Sign up to set email alerts
|

High handaxe symmetry at the beginning of the European Acheulian: The data from la Noira (France) in context

Abstract: In the last few decades, new discoveries have pushed the beginning of the biface-rich European Acheulian from 500 thousand years (ka) ago back to at least 700 ka, and possibly to 1 million years (Ma) ago. It remains, however, unclear to date if handaxes arrived in Europe as a fully developed technology or if they evolved locally from core-and-flake industries. This issue is also linked with another long-standing debate on the existence and behavioral, cognitive, and social meaning of a possibly chronological t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 93 publications
(105 reference statements)
4
56
0
Order By: Relevance
“…Quantitative studies have found that, while there are several factors that can affect biface morphology, there are discernible improvements in symmetry over the course of the Acheulean in East Africa (Schick & Toth 2017;Shipton 2018), the Levant (Grosman et al 2011a;Saragusti et al 1998), northwestern Europe (Iovita et al 2017) and India (Shipton 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative studies have found that, while there are several factors that can affect biface morphology, there are discernible improvements in symmetry over the course of the Acheulean in East Africa (Schick & Toth 2017;Shipton 2018), the Levant (Grosman et al 2011a;Saragusti et al 1998), northwestern Europe (Iovita et al 2017) and India (Shipton 2016).…”
Section: Resultsmentioning
confidence: 99%
“…However, Iovita and colleagues (Iovita et al, 2017) have recently argued that symmetry is anything but passive, rather it is a deliberately imposed feature on handaxes from Brinay la Noire on the Cher river, in the middle reaches of the Loire basin. Those from the lower level, stratum B, are c. 700 kya and represent the earliest securely contextualised and dated Acheulean handaxes yet found in western Europe.…”
Section: Methodsmentioning
confidence: 99%
“…In which case symmetry may reflect the bauplan of earlier hominin migrants (Bridgland and White, 2015). One new and important factor is raised by Iovita et al (2017). Where and when in its life cycle, and at what kind of site a handaxe is discarded or lost influences the modern interpreter's view of symmetry, because it may vary with different locations in the landscape.…”
Section: Methodsmentioning
confidence: 99%
“…The latter strategy also employed specialist grinding stones during the preparation of flake platforms. The terms EAH and LAH used here refer to general increases in flaking extent, shaping, volume control, symmetry, the use of intentional ‘thinning’ flakes, soft-hammer percussion and prepared flake platforms in later Acheulean handaxes ( Saragusti et al, 1998 ; Schick & Clark, 2003 ; Grosman, Goldsmith & Smilansky, 2011 ; Diez-Martín et al, 2014 ; Stout et al, 2014 ; Gallotti & Mussi, 2017 ; Iovita et al, 2017 ; Shimelmitz et al, 2017 ). While these differences are often clearest when tools produced >1 Mya are compared to those produced after ∼0.5 Mya, we do not mean to imply uniform linear progression of forms across regional records ( Vaughan, 2001 ; Gowlett, 2013 ; Moncel et al, 2015 ; McNabb & Cole, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…Bifaces go on to typify the next >1 million years of the archaeological record across the Old World ( Lycett & Gowlett, 2008 ; Gowlett, 2015 ; Moncel et al, 2015 ) until the onset of Middle Palaeolithic technologies ∼300 Kya ( Moncel et al, 2011 ; Tryon & Faith, 2013 ; Adler et al, 2014 ). The nature and extent of any chronological changes to stone technology during the Acheulean are debated (e.g., Vaughan, 2001 ; Chauhan, 2009 ; Gowlett, 2011 ; McNabb & Cole, 2015 ; Moncel et al, 2015 ; Gallotti, 2016 ), however, there are indications that later Acheulean bifacial tools (handaxes in particular) were at times produced using soft-hammer percussion, became thinner relative to their width (more ‘refined’), displayed greater evidence of intentional thinning, volume control (mass distribution), investment (e.g., time, skill), shaping and symmetry ( Gowlett, 1986 ; Saragusti et al, 1998 ; Schick & Clark, 2003 ; Grosman, Goldsmith & Smilansky, 2011 ; Beyene et al, 2012 ; García-Medrano et al, 2014 ; Li et al, 2018 ; Moncel et al, 2016 ; Gallotti & Mussi, 2017 ; Iovita et al, 2017 ; Shimelmitz et al, 2017 ), and at times displayed evidence of platform preparation prior to a flake’s removal ( Stout et al, 2014 ). Together, these technologies describe ∼3 million years of stone tool production and use during the Lower Palaeolithic.…”
Section: Introductionmentioning
confidence: 99%